Personal Privacy of Digital Wallet Tool-Based Payment Under Vietnam Law Perspectives - Lieu, Ta Quoc (International e-journal of criminal sciences, 2021)
Cashless payment via digital wallet tools is recognized as an increasingly developed and popular trend in Vietnam. As a result, a series of social relationships which are developed and modified should be governed by a more comprehensive legal framework, especially privacy protection of individuals involving in such legal relationships. The article focuses on assessment and analysis of following contents: Clarification of concept, connotation and characteristics of privacy in the legal relationship of digital wallet-based payment; analysis and assessment of the existing conditions of personal privacy protection regulations under the applicable Laws of Vietnam; last but not least, recommendations on perfecting the personal privacy protection laws.